Enhancing Water Resources Management with Open-Source Remote Sensing: Flood Mapping and Climate Change Insights on Kupa River case area - O. Bjelotomić Oršulić; S. Šamanović; M. Kovilić; D. Markovinović (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Flooding is one of the most damaging natural disasters, intensified by climate change, urban development, and land-use changes. Effective flood monitoring and management are crucial to mitigating the negative impacts, especially in regions with complex hydrological dynamics. This study focuses on the Kupa River basin in Croatia, a flood-prone region, and presents an integrated approach for flood mapping and climate impact assessment using open-source Earth observation (EO) data and free tools. Combining a different remote sensing datasets; Sentinel-1 Synthetic Aperture Radar (SAR), Sentinel-2 Normalized Difference Vegetation Index (NDVI), and Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS) precipitation datasets, all accessed through Google Earth Engine (GEE), this research demonstrates a cost-effective and scalable solution for monitoring flood dynamics and climate change insights on a focused area. Sentinel-1 SAR, with its cloud-penetrating capabilities, is used to detect surface water changes, while Sentinel-2 through the NDVI complemented vegetation health before and after flood events. CHIRPS data, with daily precipitation estimates, contextualizes the meteorological conditions that contribute to flooding. The integration of these datasets offers a comprehensive analysis of flood events and their environmental impacts, providing actionable insights for local flood management and climate change adaptation. The use of open-access and freely available data and free tools highlights the potential for replicable flood monitoring in regions with limited infrastructure, further supporting the development of early-warning systems and informed decision-making.